Meningkatkan Kemampuan Berbicara Anak Usia 5-6 Tahun Melalui Metode Bermain Peran di PAUD Dara Bhakti Kabupaten Cianjur - Nuryanti Nuryanti; Ibnu Hurri; Indra Zultiar (PT. Alahyan Publisher Sukabumi, 2025)
This study was Motivated by the researcher's initial findings that the speaking ability of children aged 5-6 at PAUD Dara Bhakti had not yet emerged. This can be seen from 15 students at PAUD Dara Bhakti. Data obtained around 66.7% or as many as 10 children were still included in the category of children who had not developed, then 2 children were said to be starting to develop or around 13.3% while in children who developed according to expectations only around 20% or around 3 students and no children were found with very good development. Seeing this situation is very unfortunate, because children's speaking abilities include correct pronunciation, simple sentence structure, vocabulary, fluency, and good understanding. In order to improve speaking abilities in children aged 5-6 years, researchers plan to use a role-playing method in learning that aims to improve speaking abilities in early childhood at PAUD Dara Bhakti. In this study, the Classroom Action Research (CAR) method was Used using 2 cycles where each cycle was carried out five times with different role-playing themes. The results of the study showed that the role-playing method Can improve speaking abilities by 80%. The increase in the percentage of speaking ability in children aged 5-6 years from before the action from 6.7% to cycle I to 26.7% increased by 20%. Then from cycle I 26.7% to cycle II to 80% increased by 53.3%